Clays and Clay Minerals, Vol. 60, No. 1, 40–51, 2012. - Nguyen, The-bao; Lee, Chulho; Lim, Jeehee; Choi, Hangseok (The Clay Minerals Society, 2012)
Bentonite cake is usually formed on the excavated trench surface that is supported by the bentonite slurry during construction of slurry cutoff walls. The lower hydraulic conductivity of bentonite cakes formed during construction of slurry cutoff walls in comparison to backfill materials provides an additional benefit. In the present study, the hydraulic conductivities of bentonite cakes made using three different bentonites were estimated using the modified fluid-loss test under various pressures. Both the hydraulic conductivities of bentonite cakes and cutoff-wall backfill are important in evaluating the in situ hydraulic performance of slurry cutoff-wall construction. Three bentonite slurry concentrations of 4, 6, and 8% were used to fabricate bentonite cakes that represent common field conditions. X-ray diffraction, cation exchange capacity, and swell-index data were collected to characterize the bentonites. Two modified methods for analyzing fluid-loss test results were used to estimate bentonite cake hydraulic conductivities. In addition, the viscosity as a function of time was measured to explain the sealing capacities of the bentonite slurries. The bentonite-cake hydraulic conductivities ranged from 2.15610-11 m/s to 2.88610-10 m/s, which were 10 to 500 times lower than the cutoff wall backfill design. Experimental results for 4 and 6% bentonite slurries were relatively similar, but the 8% slurries were noticeably different. Calculated bentonite-cake thickness and stress distribution indicated that the local void ratio and hydraulic conductivity may vary across the cake thickness. The considerably lower bentonite-cake hydraulic conductivities compared to the cutoff wall backfill design show its significance in slurry cutoff-wall construction practices.
Hydraulic Characteristics Of Bentonite Cake Fabricated On Cutoff Walls
gsccm60104-ngu.pdf -- 643KB
Keywords: Periodicals; Geology; Bentonite Cake; Bentonite Slurry; Cutoff Wall; Hydraulic Conductivity; Modified Fluid-loss Test; Viscosity